Anomalous Origin of Coronary Artery from the Contralateral Aortic Sinus - Case Report - Karmoker, Kajal Kumar; Siddika, Khandaker Aisha; Hossain, Arif; Javed, Mohammad Adib Al; Datta, Bijoy (University Heart Journal, 2018)
Congenital coronary artery anomalies are rare heart defect that has been associated with myocardial ischemia and sudden death. Only 1-2% of population having variation in the origin, course or distribution of the epicardial coronary arteries. Anomalous origin of coronary arteries may be present as isolated defect or as a part of complex congenital heart disease. The clinical presentation, diagnostic work up, prognosis and treatment of these anomalies are highly variable. Most of the patients are asymptomatic but manifestation of these patients are chest pain, dyspnoea, palpitation, dizziness, ventricular fibrillation, syncope and sudden death. It is the second most common cause of sudden death in young athletes. Selective coronary angiography is the gold standard for identification of such type of anomaly. Patients of anomalous origin of coronary artery from the opposite sinus may require medical treatment, coronary angioplasty with stenting or surgical repair. University Heart Journal Vol. 12, No. 2, July 2016; 98-101